Eksperimen Upcycling Limbah Koran Bekas Sebagai Material Produk Interior - Charles Hartanto; Yusita Kusumarini; Filipus Priyo Suprobo (Intra, 2019)
Newspaper production produce tons of waste and keep increasing. Although the waste generated will be recycled for next newspapers production, the fiber contained in the paper will degenerate in each cycle. The problems in this research ari how to process newspaper waste into new material for interior product with upcycling principle and discovering the possibilities of interior products that can be made with newspaper waste. Solving the problem stated were the aim of this research. To reach the optimal target, this research used experimental method which used simple characteristic testing techniques and used mixed method approach between quantitative and qualitative approach. The result of this research are newspaper tube sheets, which are made from sticking the rolled newspapers until it become sheet form using  white glue solution that consist from one part water and four part white glue. The newspaper tube sheets will be applied based on 3 axis pressure point which functions are as a pedestal, structure, and system. The furniture that will be made to represent 3 functions above are stool, coffee table, and table with sliding doors. This research proved that newspaper waste can be used again using upycling principle to become new material that can be used for interior products.